Morphological variants of meibomian glands: correlation of meibography features with histopathology findings. Issue 2 (20th August 2021) - Singh, Swati; Naidu, Gorrepati C; Vemuganti, Geeta; Basu, Sayan
Abstract : Purpose: This study describes the histopathological features of different morphological variants of human meibomian glands (MGs) seen on infrared imaging. Methods: Tarsal plates dissected from seven cadaveric upper eyelids were imaged using infrared meibography, and then studied histopathologically using H&E, peroxisome proliferator-activated receptor gamma (PPARγ, meibocyte differentiation marker) and Ki-67 (cellular proliferation marker) antibody staining. The different morphological characteristics (varying size and shape) of MGs on meibography were correlated with histopathology findings using image analysis software. Results: Of the total 127 glands, the morphological variants observed on meibography based on size were: normal (n=62), short (n=18), severely short (n=6) and dropout (n=12) glands, and on shape were: hooked (n=2), tortuous (n=5), overlapping (n=1), thick (n=15) and fluffy (n=6) glands. Short, hooked, tortuous and overlapping glands had similar acinar and ductal histology as seen in normal glands whereas thick, and fluffy glands had increased acinar diameter. All glands except the severely short type demonstrated normal signs of holocrine secretory activity and normal nuclear and cytoplasmic PPARγ expression. Severely short glands had nil while short glands had reduced Ki-67 proliferation index (3%±1%) as compared with normal and other variants (8%±5.2%). Gland dropout areas showed no evidence of any glandular tissue on histology. Conclusion: Hooked, tortuous and overlapping glands had completely normal glandular histology, whereas severely short glands showed atrophic changes with loss of meibocyte differentiation and cellular proliferation. Dropout areas showed total loss of glandular elements. Further studies are needed to validate and to explore the clinical implications of these findings.